Determinants of European wage differentials: a microeconomic analysis - Pereira, João Manuel (2016)
In this paper we further investigate the determinants of wage differences in Europe, by decomposing countries’ wage differences across the wage distribution. Unlike previous studies, we analyse the contribution of covariates to the wage decomposition components (wage structure and wage composition) by employing a recent methodology proposed by Firpo et al (2009) and Fortin et al. (2011). We use data from the EU-SILC data base for male workers from 9 European countries. We conclude that both wage structure and wage composition effects contribute to explaining wage differentials, but that wage structure is more important. Differences in the estimated constant seem to be the most significant factor explaining the importance of the wage structure effect. The differences in the composition effect, in turn, are explained by differences in education, in occupational structure, in the percentage of workers with supervisory responsibilities and to a lesser extent by differences in the industrial structure and in workers’ level of experience.